2021
DOI: 10.1029/2020ja028026
|View full text |Cite
|
Sign up to set email alerts
|

CSES High Precision Magnetometer Data Products and Example Study of an Intense Geomagnetic Storm

Abstract: The China Seismo-Electromagnetic Satellite (CSES, Shen et al., 2018), also named ZH-1, was successfully launched on February 2, 2018 on a near polar Sun-synchronous (ascending/descending local times of 02:00/14:00) orbit with an initial altitude of 507 km and an inclination of 97.4°. It has a 5-day revisiting period and the orbit distribution during a whole revisiting period from August 26-30, 2018 is shown in Figure 1. Eight scientific instruments are assembled on CSES, to obtain measurements of the magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…To obtain convincing seismo-ionospheric evidence, we pay considerable attention to data cleaning and data quality control before seismic information extraction. We have performed specific validations on CSES data, and some works about the data quality of the electromagnetic field [37,39,40] and the plasma data [31,41] have been published.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain convincing seismo-ionospheric evidence, we pay considerable attention to data cleaning and data quality control before seismic information extraction. We have performed specific validations on CSES data, and some works about the data quality of the electromagnetic field [37,39,40] and the plasma data [31,41] have been published.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we analyzed data recorded by the HPM payload onboard the CSES referring to ground-based data. HPM vector and scalar data are obtained by the Fluxgate Magnetometer (FGM) and Coupled Dark State Magnetometer (CDSM) probes, respectively [30]. In this study, HPM_5 vector data recorded by the FGM probe were selected for seismic analysis.…”
Section: Data Selectionmentioning
confidence: 99%
“…2023, 15, 4578 2 of 11 work together to provide magnetic field measurements from DC to ~15 Hz. Previous scientific studies have shown very good usability of the magnetometer data [7][8][9]. In-flight calibration based on the CDSM's scalar data is in principle well established and the quality is already very good.…”
Section: Introductionmentioning
confidence: 96%